Defining a New Business Model for Sustainable Biomass Production from Forestry Residues in Türkiye by Using TRIZ - Danisman, Murat; Akkartal, Erkut (International Journal of Energy Economics and Policy, 2023)
Global Energy demand is growing steadily. However, the world’s primary energy resources are fossil fuel based, and they are finite. Furthermore, it causes irreparable damage to the precious environment. Therefore, energy resources need to shift towards renewables, which can deliver sustainable growth and a climate-neutral outcome. While Türkiye has been quickly adopting renewable energy sources for power generation, it has yet to see opportunities for biomass generated from forestry residues readily available in abundant supply with an estimated quantity of about 5 million tons. However, most of this residue is left untouched in the forest due to a perceived lack of demand for this resource. This study aims to define a new business model for sustainable biomass production from forestry residues that will overcome this false perception. The new model was defined by using a creative problem-solving method, known as the Theoria Resheneyva Isobretatelskehuh Zadach (TRIZ). Through the semi-structured interviews with open-ended questions, the authors analyzed the responses by qualitative data content analysis (QDCA) to serve the rules of TRIZ. The new business model requires employing a small business unit (SBU) approach. It contains the involvement of forest villagers (FVs) engaged in a self-employment structure and regulated by the authorities.